CHIRP Seismic Data from the Yakutat and Disenchantment bays, Alaska, acquired during R/V Alaskan Gyre survey AG1208 (2012) (IEDA: Marine-Geo Digital Library, 2019)
This 2012 R/V Alaskan Gyre survey (also known as USGs field activity 2012-602-FA) collected 24-channel seismic data and CHIRP data in Yakutat and Disenchantment bays, Alaska. The purpose of the cruise was to look for active faults, particularly those related to the 1899 earthquakes in the Yakutat Bay. Funded by USGS-NEHRP grant G12-AP20009 and Consortium for Ocean Leadership grant T341A59.